Long non-coding RNA PSMB8-AS1 as a potential biomarker for postoperative recurrence in patients with Fuhrman grades 1–3 clear cell renal cell carcinoma - Chieko Baba; Hiroshi Hirata; Koichiro Hiyoshi; Takanori Tokunaga; Nakanori Fujii; Kosuke Shimizu; Keita Kobayashi; Takahide Hayano; Yoshiyuki Asai; Koji Shiraishi (PLoS ONE, 2026)
Long non-coding RNAs (lncRNAs) are important regulators of oncogenesis. In this study, we investigated the tumor-promoting role and prognostic value of the lncRNA PSMB8-AS1 in renal cell carcinoma (RCC). Using lncRNA microarray analysis, we identified PSMB8-AS1 as a candidate gene associated with disease progression and immune checkpoint inhibitor resistance. We examined PSMB8-AS1 expression in tumors and adjacent normal renal tissues from 192 patients with RCC. In vitro functional assays were performed to assess their role in cell proliferation and invasion. We also conducted bioinformatics and luciferase reporter assays to clarify the interaction between miR-204-5p/miR-211 and the transcription factor TFAP2A. PSMB8-AS1 was significantly overexpressed in clear cell RCC (ccRCC) tissues and correlated with poor prognosis. Knockdown experiments revealed that PSMB8-AS1 promoted proliferation and invasion. Mechanistically, PSMB8-AS1 functions as a competing endogenous RNA, sponging miR-204-5p/miR-211 and enhancing TFAP2A expression. These findings suggest that PSMB8-AS1 represents a promising biomarker for postoperative ccRCC recurrence.